2007
DOI: 10.1093/cvr/cvm011
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and tachycardia increase NADPH oxidase and ryanodine receptor-2 activity: possible role in cardioprotection

Abstract: The loss of cardioprotection induced by the NADPH oxidase inhibitor suggests that ROS generated by this enzyme are important mediators of the preconditioning response, which presumably involves NADPH oxidase-induced RyR2 S-glutathionylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 30 publications
3
88
1
Order By: Relevance
“…We can hypothesize that a small amount of reactive oxygen species produced during each bout of exercise may trigger the cardiac adaptations. Indeed, studies have demonstrated that cardioprotective effects of exercise or tachycardia were abolished when anti-oxydants are given during exercise [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can hypothesize that a small amount of reactive oxygen species produced during each bout of exercise may trigger the cardiac adaptations. Indeed, studies have demonstrated that cardioprotective effects of exercise or tachycardia were abolished when anti-oxydants are given during exercise [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This might partly explain potential beneficial adaptations of calcium handling with exercise. Indeed, it has been previously reported that exercise increases ryanodine-S-glutathionylation which inhibits ryanodine-mediated calcium leak [38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, Sanchez et al [43] reported the presence of Nox2 NADPH oxidase activity in canine cardiac SR and showed that oxidase activation increased S-glutathionylation of ryanodine receptors and hence SR Ca2+ release -effects which were abrogated by apocynin (a purported Nox inhibitor, but which may act as a non-selective antioxidant). The same group also showed that oxidase activity and the effects on SR Ca2+ release were augmented by tachycardia [44]. O2−radical dot produc on by NADPH oxidase on the SR of bovine coronary artery smooth muscle cells has also been shown to regulate calcium-induced calcium release [45].…”
Section: Effects Of Nadph Oxidase On Calcium Signalingmentioning
confidence: 93%
“…However, the myocardium of Nox2−/− mice could s ll be preconditioned by an adenosine receptor agonist. Subsequently, other groups have reported an involvement of NADPH oxidase-derived ROS in the cardiac preconditioning induced by angiotensin II [111] and [112] and tachycardia or exercise [43] and [44].…”
Section: Ischemic Preconditioningmentioning
confidence: 99%
“…Collectively, the activation of these signaling cascades thus could lead to vasodilation, cell proliferation, injury, or other consequences (17,26,73,142). As ROS and NO are able to modulate thiol groups of many ion channels (1,27,101) including the K ATP channel (21,64,138), which are potentially involved in membrane potential regulation and downstream signaling, we propose that a feedback loop may exist linking membrane potential, ion channel regulation (by S-glutathionylation or S-nitrosylation), The modification of one cysteine by S-glutathionylation has an allosteric effect on another cysteine residue at a different place, modulating its reactivity to S-nitrosylation.…”
Section: Ion Channels In Mechanotransduction and Possible Contributiomentioning
confidence: 99%